Subclinical Vascular Disease Burden and Premature Mortality Among Middle-aged Adults: the Atherosclerosis Risk in Communities Study - Wu, Chenkai; Zhang, Kehan; Odden, Michelle C.; Kucharska-Newton, Anna M.; Palta, Priya; Matsushita, Kunihiro; Gottesman, Rebecca F.; Windham, B. Gwen (Journal of general internal medicine : JGIM, 2021)
Background Whether high burden of subclinical vascular disease (SVD) is associated with increased premature mortality among middle-aged adults is not adequately understood. The association of midlife SVD burden with premature mortality among middle-aged adults free of clinical cardiovascular disease (CVD) could provide further insights into stratifying premature death beyond clinical CVD. Objective To determine whether high burden of subclinical vascular disease is associated with increased premature mortality among middle-aged adults. Design We leveraged data from the Atherosclerosis Risk in Communities Study. Participants Thirteen thousand eight hundred seventy-six community-dwelling blacks and whites aged 45–64 years from the Atherosclerosis Risk in Communities Study. Main Measures Each SVD measure—ankle-brachial index, carotid intima-media thickness, and electrocardiogram—was scored 0 (no abnormalities), 1 (minor abnormalities), or 2 (major abnormalities). An index was constructed as the sum of three measures, ranging from 0 (lowest burden) to 6 (highest burden). We used the Cox proportional-hazards model to determine the association of SVD burden with premature mortality (death before age 70) among persons free of clinical CVD. We then tested the difference in point estimates between SVD and clinical CVD. Key Results Among persons without CVD, the premature death was 1.7, 2.1, 2.5, and 3.8 per 1000 person-years among those with an SVD score of 0 (lowest burden), 1, 2, and 3–6 (highest burden), respectively. After multivariable-adjustment, highest SVD burden (score = 3–6; HR = 1.47) was significantly associated with premature death among persons initially without CVD. In the model where persons with and without CVD were included, high SVD burden (score: 3–6 vs. 0) and CVD did not have hugely different association with premature death (HR = 1.49 vs. 1.68; P = 0.32 for comparison). Conclusions Midlife SVD burden was associated with premature mortality and it could stratify premature death beyond clinical CVD. It is important to take SVD into account when designing interventions for reducing premature mortality.